The Relationship between Teachers' Teaching Styles and Students' Learning Motivation in Physical Education Learning - Alif Aryadi Hardi (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2026)
The quality of teaching in elementary education plays a critical role in shaping students’ engagement and motivation, particularly in practical subjects such as physical education, sports, and health. Teaching style is considered a key pedagogical factor that can influence how students perceive, respond to, and participate in the learning process. This study aims to determine the relationship between teacher teaching style and student learning motivation in physical education, sports, and health learning in Jeppe'e 23 state elementary schools. The study used a quantitative approach with a correlational design. The study population consisted of 69 students in grades IV, V, and VI, with a sample of 30 students determined through simple random sampling. Data collection was conducted using a Likert-scale questionnaire on teacher teaching style and student learning motivation. Data were analyzed using descriptive analysis and Pearson Product Moment correlation. The results showed that the teacher’s teaching style was in the good category, while student learning motivation was in the high category. The correlation test showed a positive and significant relationship between teacher teaching style and student learning motivation in physical education, sports, and health learning, with a correlation coefficient of r = 0.62 and a significance value of p < 0.05. These findings indicate that the better the teacher's teaching style applied in physical education, sports, and health learning, the higher the student's learning motivation. Based on the research results, it can be concluded that teacher teaching style plays a crucial role in enhancing student learning motivation in elementary schools. Therefore, physical education, sports, and health teachers are expected to develop varied, communicative, and student-specific teaching styles to create effective and enjoyable learning